Stakeholder interactions of government intervention in construction and demolition waste recycling market: A game theory approach - Su, Yangyue; Xu, Yabing; Bao, Zhikang; Ng, S. Thomas; Gao, Qun (Developments in the built environment, 2024)
To acquire an in-depth understanding on how government intervention affects C&DW recycling market, this study develops four game models consisting of three main categories of stakeholders, e.g., the government, contractors, and C&DW receivers (recycling enterprises and landfills) to reveal stakeholder interactions of government intervention. Taking China's C&DW recycling market as an example, four different scenarios are established to examine and compare the effects of government intervention policies on C&DW recycling, illegal dumping, and stakeholder profits. Finally, numerical simulations are performed to gain further insights into the impact of government intervention on stakeholders' behaviors with a case study from Shenzhen, China. Results indicate: (1) government intervention policies can always lead to an increased amount of C&DW recycled and a reduced amount of C&DW illegally dumped compared to no any measure; (2) government subsidy can improve the market competitiveness of recycling enterprises and weaken the competitiveness of landfills. Both subsidy-only and subsidy-plus-penalty policies help reduce economic burden on contractors compared to no interventions, but penalty policy increases contractors' expenditures. Finally, penalty policy can significantly reduce the amount of illegally dumped C&DW, while subsidy policy can significantly increase the amount of recycled C&DW. This study provides valuable theoretical support and practical guidance for decision-making of governments in developing economies to develop C&DW recycling by formulating targeted intervention policies. •Stakeholder interactions of government intervention in C&DW recycling are explored.•Four game models involving three main categories of stakeholders are constructed.•Simultaneous adoption of subsidy and penalty policy can curb market failures.•Subsidy leads to increasing C&DW recycled and decreasing C&DW landfilled.•Penalty helps regulate illegal dumping and improve performance of C&DW receivers.